Sustaining Work Life Balance of Senior High School Principal and Teacher - Hadiyansyah, Mohammad Nur (Universitas Muhammadiyah Tangerang, 2025)
This study employed a phenomenological approach to investigate the experiences of principals and teachers in Indonesia in achieving work-life balance and well-being. The findings revealed that principals and teachers face various challenges that can negatively impact their work-life balance, including heavy workloads, high expectations, limited resources, and a lack of work-life balance. On the other hand, the study also identified several positive aspects of working in schools that can contribute to enhanced well-being, such as a collaborative culture, a sense of purpose, and building relationships with students. Based on the research findings, recommendations are presented to promote work-life balance for principals and teachers in Indonesia. These recommendations include enhancing support, leadership development, collaboration, workload reviews, mental health resources, flexible work arrangements, and a culture that values personal time.